Antimicrobial Peptides-Loaded Hydroxyapatite Microsphere With Different Hierarchical Structures for Enhanced Drug Loading, Sustained Release and Antibacterial Activity - Hong, Dandan; Wu, Jingjing; Xiao, Xuemin; Li, Xueyang; Xu, Dong; Du, Chang (Frontiers in Chemistry, 2021)
Antimicrobial peptides (AMPs) have great potentiality for clinical treatment of bacterial infection due to the broad-spectrum and highly effective antibacterial activity. However, the easy degradation and inactivation in vivo has been a major obstacle for their application and an effective delivery system is demanding. The surface physicochemical properties of the carrier, including surface potential, surface polarity, pore structure and morphology, have exerted great effects on the adsorption and release behavior of AMPs. This study investigated the influence of micro/nano carriers with different hierarchical structures on the loading, release and biological behavior of AMPs. Three types of AMPs-loaded hydroxyapatite microspheres (HA/AMPs MSs) with different hierarchical structures (needle-like, rod-like, and flake-like) were developed, which was investigated by the surface morphology, chemical composition and surface potential in detail. The different hierarchical structures of hydroxyapatite microspheres (HA MSs) had noticeable impact on the loading and release behavior of AMPs, and the flake-like HA MSs with hierarchical structure showed the highest loading efficiency and long-lasting release over 9 days. Meanwhile, the stability of AMPs released from HA MSs was effectively maintained. Moreover, the antibacterial test indicated that the flake-like HA/AMPs MSs showed more sustained antibacterial properties among three composites. Therefore, in view of the excellent biocompatibility and osteogenic property, high loading efficiency and the long-term release properties of HA MSs with hierarchical structure, the HA/AMPs MSs have a great potential in bone tissue engineering.